2008
DOI: 10.1021/nn800200d
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Conductive Single-Walled Carbon Nanotube Networks with Precisely Tunable Ratios of Semiconducting and Metallic Nanotubes

Abstract: We present a comprehensive study of the optical and electrical properties of transparent conductive films made from precisely tuned ratios of metallic and semiconducting single-wall carbon nanotubes. The conductivity and transparency of the SWNT films are controlled by an interplay between localized and delocalized carriers, as determined by the SWNT electronic structure, tube-tube junctions, and intentional and unintentional redox dopants. The results suggest that the main resistance in the SWNT thin films is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

29
359
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 302 publications
(392 citation statements)
references
References 40 publications
29
359
2
Order By: Relevance
“…Hence, if we are able to increase the number of the effective electric conductive tube-tube junctions per unit area without increasing the number of the SWCNTs, we will improve the transport of free carriers between the tubes and lower the percolation threshold, thus improving the conductivity of the CNT networks. Recent work by Blackburn et al [14] supports this analysis. Those workers found that the DC conductivity of the SWCNT film is several orders of magnitude lower than expected by considering the total carrier density within the conduction band of individual SWCNTs (approximately 1 electron per carbon atom).…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…Hence, if we are able to increase the number of the effective electric conductive tube-tube junctions per unit area without increasing the number of the SWCNTs, we will improve the transport of free carriers between the tubes and lower the percolation threshold, thus improving the conductivity of the CNT networks. Recent work by Blackburn et al [14] supports this analysis. Those workers found that the DC conductivity of the SWCNT film is several orders of magnitude lower than expected by considering the total carrier density within the conduction band of individual SWCNTs (approximately 1 electron per carbon atom).…”
mentioning
confidence: 61%
“…T h em a i nc h a l l e n g eh e r ei st oa d d r e s st h et r a d e -o f fb e t w e e n transparency and conductivity. Many factors have been studied in order to improve the conductivity of the CNT thin films without sacrificing their transparency [4,[11][12][13][14][15]. For example: processing techniques and parameters [4,11]; length of the CNT [12]; doping [13,14]; and metallic amount of the CNT in the mixture [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent report, 10 we provided unambiguous evidence of bulk enrichment of armchair nanotubes through DGU by utilizing wavelength-dependent resonant Raman scattering spectroscopy. We found that the Raman spectra were dominated by (6,6), (7,7), (8,8), (9,9), and (10,10) for samples enriched from carbon nanotubes synthesized by the high-pressure carbon monoxide (HiPco) method.We studied the absorption properties of a series of armchairenriched samples with different diameter distributions, exhibiting distinct colors (see Fig. 1).…”
mentioning
confidence: 99%
“…Compared to the commonly used indium tin oxide electrodes, nanotube films show lower resistance for the same transparency level. 34,35 Another interesting application of carbon nanotubes is in chemical and biological sensors. Since all of the carbon atoms are on the surface, SWNTs are highly sensitive to their environment.…”
Section: Nano Focusmentioning
confidence: 99%